IMPLEMENTASI PEMBELAJARAN KIMIA BERBASIS LINGKUNGAN DENGAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKATKAN MINAT DAN KETERAMPILAN BERPIKIR KRITIS PADA SISWA SMA (Lantanida Journal, 2017)
This study aims to analyze: (1) the difference between the critical thinking skills that students learn through the implementation model of Problem Based Learning (PBL) environment based on petroleum materials with students who learn through conventional learning model (2) differences in student interest through implementation model (PBL) environment based on the students' interest through conventional learning models. This study was a quasi-experimental research in class X of SMA KARTIKA XIV-1 BANDA ACEH in Academic Year 2013/2014. The research design was a two-group pretest-posttest design. Data were analyzed by independent t-test statistical analysis test with the software program SPSS version 17. The results obtained by analysis of the percentage of the average value of the initial test experimental class is 25.00 and 24.69 for the control class. Furthermore, the percentage of the average value of the final test in the experimental class at 77.35, while the control class is 62.19. The average N-gain normalized experimental class were high with an average rating of 0.75 while the control class including medium category with an average rating of 0.50. For N-normalized gain obtained t = 6.045 with signfikansi p = 0.000, due to the significance
Keywords: Problem Based Learning (PBL); Student Interest; Critical Thinking Skills.